(untitled) (Mustansiria Dental Journal, 2025)
Background: This in vitro study compared and evaluated the effects of various irrigation solutions on the root canal dentin’s microhardness, including Triton, 0.5% chitosan nanoparticles (CNP), and 17% ethylenediaminetetraacetic acid (EDTA). Materials and Methods: Forty extracted mandibular premolars were selected; the samples were decorated to establish 14 mm root length. Each sample was instrumented by using ProTaper Next rotary file X4 (40/0.06). After instrumentation, based on irrigation solution, the samples were randomly split into four groups (n = 10). Group I(Triton), group II (0.5% CNP), group III:(17% EDTA), and group IV:( distal water). The samples were rinsed by Triton throughout instrumentation with Triton and final irrigation for 1.5 min by 1 ml of Triton, CNP, EDTA, and distal water were rinsed with final irrigation by 5 ml of 0.5% CNP, 17% EDTA and distal water for 3 minutes respectively. The samples were longitudinally sectioned and examined under a Vickers microhardness test in the coronal, middle, and apical thirds. The mean of these three-thirds was used to determine the microhardness of each sample. ANOVA test was used for statistical evaluation. Results: There was a significant difference (p≤ 0.05) between all evaluated irrigating solutions, Triton demonstrated the lowest mean of reducing the microhardness compared to the other irrigation solutions followed by CNP and EDTA which had the highest mean of decreasing the root dentin’s microhardness. Conclusions: Compared to the other irrigation solutions examined in this study, Triton had less of an impact on microhardness. EDTA demonstrated the highest effect on root dentin microhardness compared to the other irrigation solutions.